2013
DOI: 10.1149/05013.0043ecst
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FTIR Characterization of Growth Inhibition in Atomic Layer Deposition Using Reversible Surface Functionalization

Abstract: The layer-by-layer nature of ALD allows precise control of surface composition in the growth direction normal to the surface. However, it is harder to control the amount of material incorporated during a single ALD cycle. Recently, we demonstrated an approach based on incorporating an in-situ surface functionalization step into each ALD cycle.[1] This step essentially controls the amount of reactive sites on the surface, ideally modulating the saturation coverage while maintaining the self-limiting surface che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Some in situ experimental studies have elucidated the reaction of alcohols with surface-adsorbed precursors. In previous studies on ALD Al 2 O 3 and ZrO 2 with EtOH oxidants, surface ethoxy groups were observed during the ALD cycle. In other studies, dealing with the reaction of alcohols on alumina surfaces, various alcohols were adsorbed on the alumina surface through the formation of various alkoxides.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Some in situ experimental studies have elucidated the reaction of alcohols with surface-adsorbed precursors. In previous studies on ALD Al 2 O 3 and ZrO 2 with EtOH oxidants, surface ethoxy groups were observed during the ALD cycle. In other studies, dealing with the reaction of alcohols on alumina surfaces, various alcohols were adsorbed on the alumina surface through the formation of various alkoxides.…”
Section: Results and Discussionmentioning
confidence: 88%
“…Fortunately, this can be estimated from the HertzKnudsen equation: = 789:; 9< = > = ? (@AB) [4] t sat = surface saturation time M = molar mass of the precursor k = Boltzman constant T = temperature d = precursor molecule diameter, assuming spherical geometry for the molecule S = sticking coefficient of the precursor molecule when hitting an active surface site = fractional surface coverage = fraction of already reacted surface sites (1-) = probability for the precursor molecule hitting an active surface site p = precursor partial pressure above the substrate An example calculation is presented graphically in Figure 5. It can be seen that the reaction rate can be the limiting factor for the minimum pulse time only with very unreactive precursors.…”
Section: Surface Reaction Of the Precursor Molecules With The Substratementioning
confidence: 99%
“…Also sometimes the precursor cannot be synthesized in pure form, but is delivered in a solvent or as an adduct containing both the precursor molecule and the solvent molecule used in its synthesis. Upon vaporization the solvent molecules are also released to the gas phase and transported to the reaction chamber where they may interfere with the ALD surface chemistry, for example by poisoning the active sites on the substrate [4]. The extent at which the solvent molecules are vaporized along with the precursor molecules, or whether the adduct is vaporized as one molecule or decomposed to the precursor and solvent molecules, depends on the saturation vapor pressure and vaporization kinetics of the solvent versus the precursor.…”
Section: Precursor Puritymentioning
confidence: 99%
“…Quantitative analysis with variations in oxygen sources and subcycle sequences reveals the dependences of the film compositions and growth rate on surface chemistry and oxygen sources (O 3 or H 2 O). The systematically designed analysis introduced here serves as complementary information to the results from in situ diagnostic studies such as the quartz crystal microbalance, quadrupole mass spectrometry, ,, Fourier transform infrared spectroscopy, , and X-ray photoelectron spectroscopy (XPS). , The current work compares the final film composition and layer density estimated using a quantitative spectroscopic technique [X-ray fluorescence spectroscopy (XRF)] to study the intermolecular reaction between the precursors and the film surface under given ALD sequences composed of different ratios of SrO and TiO 2 subcycles. A simple mathematical formula to describe the incorporation rates of Sr and Ti atoms per ALD step provides a potentially useful analytical tool to interpret the growth behavior of other multicomponent ALD process.…”
Section: Introductionmentioning
confidence: 99%